2023
DOI: 10.1021/acscatal.3c00555
|View full text |Cite
|
Sign up to set email alerts
|

Advances in One-Pot Chiral Amine Synthesis Enabled by Amine Transaminase Cascades: Pushing the Boundaries of Complexity

Abstract: Amine transaminases constitute an important class of enzymes for the synthesis of chiral amines, which are commonly used as building blocks in pharmaceutical compounds and fine chemicals. Over the past decade, developments in enzyme discovery and process and protein engineering have advanced the use of transaminases in organic synthesis. Recent advances in enzymatic cascade engineering have attracted attention due to efficient and environmentally friendly routes to synthesize chiral amines. Enzymatic cascades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Furthermore, the reaction was successfully implemented in a continuous flow system, yielding similar results in terms of yield and enantioselectivity. 194…”
Section: Classification Of Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the reaction was successfully implemented in a continuous flow system, yielding similar results in terms of yield and enantioselectivity. 194…”
Section: Classification Of Enzymesmentioning
confidence: 99%
“…Furthermore, the reaction was successfully implemented in a continuous flow system, yielding similar results in terms of yield and enantioselectivity. 194 Transaminase mediated transformations are of significant utility for the synthesis and production of fine chemicals and drug intermediates. The most extensively researched area in which transaminases have been discovered to be useful is asymmetric synthesis for the production of chiral amines, which account for about 40% of all medicinal substances.…”
Section: Tutorial Reviewmentioning
confidence: 99%
“…As a significant class of enzymes that take part in the biosynthesis of L-PPT, transaminases (EC 2.6.1.X, TAs) represent enzymes with pyridoxal-5′-phosphate (PLP) dependence, catalyzing reversible amino groups transfer between amino donor and acceptor (Guo and Berglund 2017 ; Mathew et al 2023 ; Slabu et al 2017 ). The TAs are divided into PLP fold types I and IV (Meng et al 2021 ), and TAs that belong to fold type I only appear as ( S )-enantioselective (Börner et al 2017 ; Konia et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several TAs developed for the asymmetric synthesis of L-PPT suffered low equilibrium constant, resulting in an unfavorable thermodynamic equilibrium, which further led to the inability to achieve the theoretical yield (Liu et al 2023 ; Zhu and Hua 2009 ), for example, the TA from Citrobacter koseri ( Ck TA), which showed a maximum conversion of 93.3% at 100 mM substrate concentration (Jia et al 2019 ), and the TA from Pseudomonas fluorescens ( Pf TA), which we previously reported to yield 79% L-PPT after 24 h reaction at 500 mM substrate (Jin et al 2019 ). Removal of by-product can effectively shift the equilibrium in the transamination reaction, one of the most attractive strategies was to construct an enzymatic cascade by coupling amino acid dehydrogenases (AADHs, EC 1.4.1.X) (Hepworth et al 2017 ; Mathew et al 2023 ), such as alanine dehydrogenase (AlaDH, EC 1.4.1.1) or glutamate dehydrogenase (GluDH, EC 1.4.1.2) (Wu et al 2023 ). The cascade system can regenerate amino donor with cofactor NAD(P)H, supplying amino groups through using cheap inorganic ammonia (Dave and Kadeppagari 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other enzymes in chiral amine synthesis, TAs are characterized by a broad substrate range, excellent enantioselectivity, high regioselectivity and chemoselectivity, and unique cofactor self‐cycling, which make TAs a promising class of chiral amine biocatalysts (Fuchs et al, 2010; Guo & Berglund, 2017; Patil et al, 2018b). TAs can also be used in conjunction with other biocatalysts to catalyze multistep synthesis processes, effectively reducing the number of reaction steps and enabling the production of highly stereoselective chiral products from inexpensive feedstocks (Cutlan et al, 2020; Mathew et al, 2023; Simon et al, 2013; Skalden et al, 2015).…”
Section: Introductionmentioning
confidence: 99%